Post-Eruption Economic Recovery for Semeru Survivors: The Role of Collaborative Learning in HUNTAP SEMERU Areas - Cahyaningati, Retno; Setyobakti, Hudi; Kasno, Kasno; Heni, Heni; Rouf, Abdur; Wiyono, M Wimbo (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2025)
This research aims to enhance the economic resilience of the Huntap Semeru community through collaborative learning initiatives focused on entrepreneurship, financial literacy, and innovation. The goal is to address financial constraints and empower residents to achieve sustainable economic recovery following the 2021 Mount Semeru eruption. The study employs a quantitative descriptive method to assess the differences in knowledge and skills before and after collaborative learning. A purposive sample of 10 active participants from the Huntap Semeru area was selected. Data collection involved structured questionnaires covering entrepreneurship knowledge, financial literacy, innovation capabilities, and financial constraints. Data were analyzed using descriptive statistics and Pearson correlation tests to evaluate the relationship between financial literacy, innovation, and financial constraint reduction. The findings reveal significant improvements in understanding entrepreneurship, financial literacy, and innovation post-learning. Pretest accuracy, averaging 30%, increased to over 80% in the posttest. Collaborative learning effectively bridges knowledge gaps and motivates the community to explore innovative solutions. Enhanced financial literacy equips residents to manage budgets and investments, reducing financial constraints and supporting economic sustainability. This research contributes to practical applications by offering a replicable model of community-based learning to empower disaster-affected populations.